Nationwide study of sudden cardiac death in young persons diagnosed with chronic kidney disease. (19th May 2022) - Svane, J; Nielsen, JL; Feldt-Rasmussen, B; Garcia, R; Risgaard, B; Gislason, GH; Winkel, BG; Lynge, TH; Tfelt-Hansen, J
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): This work was supported by Novo Nordisk Foundation, Copenhagen, Denmark. Background: Chronic kidney disease (CKD) is associated with increased risk of cardiovascular morbidity and mortality. The increased cardiovascular mortality is partly explained by an increased risk of sudden cardiac death (SCD) among patients with CKD. Purpose: The purpose of this study was to compare short- and long-term risk of SCD in individuals with and without CKD aged 18-49 years. Methods & Results: Using the Danish nationwide health registries, all persons aged 18-49 years diagnosed with non-failure stage CKD or kidney failure from 1st of July 1995 through 2009 were identified. Non-exposed subjects matched on sex and birth-year were included 50:1. All SCD in the Danish population aged 18-49 years in 2000-2009 have previously been identified by thoroughly examining the Danish Registries, the Danish death certificates, autopsy reports and discharge summaries. In total, 9, 476 incident cases of non-failure stage CKD and 1, 283 incident cases of kidney failure were included. For patients with non-failure stage CKD and kidney failure, the absolute risk of all-cause mortality 10-year after diagnosis was 8.7% and 23.6%, respectively. Among patients with non-failure stage CKD, the absolute risk of SCD 1, 5 and 10 years after diagnosis was 0.14%, 0.37%, and 0.68%, respectively. Compared with age- and sex matched subjects the corresponding relative risk was 20 (95%-CI 8.4-48.8), 7.1 (95%-CI 4.2-12.0), and 6.1 (95%-CI 3.8-9.7), respectively. Among patients with kidney failure, the absolute 1, 5, and 10 year risk of SCD was 0.17%, 0.56% and 2.07%, respectively. The corresponding relative risk was 12.5 (95%-CI 1.4-111.6), 7.9 (95%-CI 2.3-27.0) and 10.1 (95%-CI 4.5-22.6), respectively. Conclusions: Persons with non-failure stage CKD and kidney failure had increased risk of SCD compared with the background population with a 20- and 13-fold increased risk one year after diagnosis, respectively. These findings underline the importance of early cardiovascular risk monitoring and assessment in persons with CKD.